Volume 1: Symposia, Parts a and B 2005
DOI: 10.1115/fedsm2005-77487
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of an Industrial Pump: Application of Genetic Algorithms and Neural Network

Abstract: This paper presents an integrated environment FINETM/Design3D developed for the optimization of turbomachinery blade shapes. The methodology relies on the interaction between a genetic algorithm, an artificial neural network, a database and user generated objective functions and constraints. The optimization is coupled to the FINETM/Turbo environment of NUMECA. The present paper focuses on the application of the multipoint optimization algorithm to the design of an industrial pump. The large range of mass flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…It is well known that optimization methods based on gradients techniques are efficient in terms of convergence rate, but do not guarantee to produce the global optimum [4]. On the other hand, genetic algorithms offer the advantage of enhancing the probability of reaching the global optimum, but may require thousands of iterations [11]. Their coupling with a three-dimensional Navier-Stokes solver cannot be considered under the framework of an industrial design process.…”
Section: Initial Runner Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that optimization methods based on gradients techniques are efficient in terms of convergence rate, but do not guarantee to produce the global optimum [4]. On the other hand, genetic algorithms offer the advantage of enhancing the probability of reaching the global optimum, but may require thousands of iterations [11]. Their coupling with a three-dimensional Navier-Stokes solver cannot be considered under the framework of an industrial design process.…”
Section: Initial Runner Designmentioning
confidence: 99%
“…Each design iteration starts with the neural network learning. As the design proceeds, the database grows, leading to improvements of the approximate relation and therefore to a better localization of the real optimum [11]. The geometry parameterization is a critical element in the success of any shape optimization method.…”
Section: Initial Runner Designmentioning
confidence: 99%
“…Demeulenaere et al [1] investigated an optimization process on centrifugal pumps using Fine/ Design 3D environment of Numeca software and genetic algorithms. They tried to increase efficiency and head and decrease the NPSHr at two different flow rates and finally showed that the new blade geometry should have more curvature in the camber line definition.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of centrifugal pumps is a multi-objective optimization problem rather than a single objective optimization problem that has been considered so far in the literature. Demeulenaere et al (2005) investigated an optimization process on centrifugal pumps using Fine/Design 3D environment of Numeca software and genetic algorithms. They tried to increase efficiency and head rise and decrease the NPSHr at two different flow rates and finally showed that the new blade geometry should have more curvature in the camber line definition.…”
Section: Introductionmentioning
confidence: 99%